Penerapan Sistem Solar Cell untuk Penerangan Lampu Jalan dan Peningkatan Potensi Usaha Mikro Kecil Menengah untuk Mendukung Ketahanan Energi dan Ekonomi Masyarakat Kelurahan Manggar Balikpapan - Maria Ulfah; Andi Sri Irtawaty; Armin Armin; Dessy Handa Sari; Nurul Musfirah Khairiyah (Abdimas Universal, 2023)
The lack of access to lighting in the RT 39 area, Manggar Village, Balikpapan City, results in frequent traffic accidents for motorists crossing the road and without crimes at night or in dark conditions. It was also found that the majority of MSME actors use conventional promotions to market their business or products. Based on this, the Bina Desa Community Service team is trying to provide a solution by implementing a solar cell system as street light lighting in RT 39 and training activities on the use of digital marketing for MSMEs as a business promotion medium. The results of the implementation of Community Service activities have been the installation and functioning well of 2 units of solar panel-based street lighting in RT.39 and outreach activities regarding solar panels and how to maintain them have been carried out. There have also been training activities on the use of digital marketing for MSMEs in the Manggar area which received a positive response from the participants. In this community service activity, Bina Desa also handed over 2 units of solar panel-based village street lighting to the sub-district which were immediately received by the Head of Manggar Balikpapan Village. The results of the pre-test and post-test analysis showed a 20% increase in participants' knowledge regarding solar panels and their use, a 70% increase in knowledge about digital marketing, a 30% increase in participants' use of social media as an alternative to promoting their business or trade.